TGA16 Type IGBT Converter for High-speed Test EMUs - WENG Xing-fang; LIU Da; ZOU Dang-bing (机车电传动)
The main technical parameters, power circuit principle, structure and cooling system of the TGA16 type IGBT converter employed in the high-speed test EMUs were introduced, as well as the technical characteristics of the converter. The test proved the converter to meet operation demand of the hish-speed test EMUs.